Customer protection and money laundering in the era of digital currencies: are Malaysian regulations enough to combat? / Norazida Mohamed … [et al.] - Mohamed, Norazida; Tan, Khee En; Sultan, Nasir; Sattar, Akbar; Latiff, Hafizah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The study aimed to assess the robustness of Malaysia’s current digital currency regime by critically examining the various pieces of legislation and gathering first-hand information from stakeholders. The study used a qualitative approach to accomplish the research objectives. Semi-structured interviews with regulators, legal councils and investors were conducted to gain in-depth and practical knowledge concerning the connection among digital currencies, money laundering and customer protection. According to the study, Malaysia has positive intentions towards digital currencies concerning protection through robust legislation. However, current practices and laws enacted by the government and regulators are contradictory. It has resulted in confusion among the public concerning adopting or rejecting such currencies. Further, this confusion provided opportunities for scammers and caused the trapping of innocent investors by scammers. These loopholes and contradictions among different legislations offer a favourable environment for criminals, especially money launderers, to exploit the Malaysian digital currencies regime. Therefore, to address this situation and protect customers, authorities should clarify the roles of various regulators and educate the public about the dangers of using unauthorised digital currency platforms.